Gambaran Pengetahuan Korps Sukarela (KSR) Prodi D-III Keperawatan Blitar tentang Post Traumatic Stress Disorder (PTSD) - Mefasa Nutfa Sagita (Journal of Ners and Midwifery, 2016)
Post Traumatic Stress Disorder (PTSD) is an anxiety disorder due to excessive trauma an incident/experience scary/awful, unforgettable and unpleasant. The purpose of the research was to describe the knowledge of Volunteer Corps (KSR) of Prodi D-III Nursing Blitar on Post Traumatic Stress Disorder (PTSD). Method: The research method used descriptive design. The population in this study was all members of KSR level 1 in Prodi D-III Nursing Blitar who had passed KSR training, and the sample was 93 people taken by total sampling technique. Result: The result showed that the knowledge of Volunteer Corps (KSR) of Prodi D-III Nursing Blitar on Post Traumatic Stress Disorder (PTSD), 62.4% (58 respondents) had a good knowledge of Post Traumatic Stress Disorder (PTSD), 26.9% (25 respondents) had sufficient knowledge of Post Traumatic Stress Disorder (PTSD), and 10.8% (10 respondents) had less knowledge on Post Traumatic Stress Disorder (PTSD). Discussion: the knowledge gained from the training of KSR they once did and the information obtained from the KSR training, and other information, either formally or informally. Although most members of KSR did not have experience in dealing with PTSD, they had a good knowledge gained from training KSR and the acquired information. And conversely though it had good knowledge, they were not always able to handle PTSD because they did not have enough experience to deal with PTSD.